Staphylococcus aureus in Hemodialysis Unit: A Comparative Study between Patients and Medical Staff - Maryam A. Abraheem; Ghalia Salem M. Eswai; Fatma M. A. El-garj (African Journal of Advanced Pure and Applied Sciences, 2025)
Background: patients undergoing dialysis are more susceptible to S. aureus infection due to their health condition and the presence of medical equipment, making them vulnerable to hospital-acquired infections. This study focuses on determining the prevalence of S. aureuscolonization among patients as well as among medical staff. Results: A total of 217 samples were collected the percentage among bacterial species were S. aureus 60 (27.7%) isolated bacteria. There was significant association between age groups and infection with S. aureus (P≤ 0.05) of all positive S. aureus, the most infections occurred in the age groups (48–64 years) as compared to other age groups (24; 42.1%) of patients, as well as, the most infections occurred in the age groups (48–64 years) as compared to other age groups (8; 27.6%) of medical staff. Males showed significantly higher positive the carriage rate of S. aureus (30; 35.3%) in patients and (12; 21.8%) in medical staff as compared to females (12; 33.3%), (6; 14.6%) in patients and medical staff respectively, there was a statistical difference between the duration of disease with hemodialysis and carriers of S. aureus at P≤ 0.05. The duration of disease with haemodialysis ≤60 months were higher carriage (11; 42.3%) compared to the duration of disease with haemodialysis ≥60 months (31; 32.6%). Conclusion: this study demonstrated a high prevalence of S. aureus in the nose and hands of hemodialysis patients and medical staff in the study area. These findings, call for an urgent need to establish prevention and control measures of S. aureus among patients as well as among medical staff.